Detection and antibiotic resistance profile of extended-spectrum betalactamase—producing Escherichia coli in raw vegetables - Lee, E.; New, C. Y.; Thung, T. Y.; Tan, C. W.; Wendy R. D.; J., Nuzul N.; Son, R.; Abdul-Mutalib, N. A. (Rynnye Lyan Resources, 2023)
The increase of antibiotic-resistance bacteria in food and vegetables has heightened the concern related to food safety globally. The current study aimed to determine the prevalence and antibiotic resistance profile of extended-spectrum beta-lactamase (ESBL)-producing Escherichia coli in raw vegetables. This study coupled the most probable number (MPN) method with multiplex polymerase chain reaction (mPCR) to determine the presence and enumerate the ESBL-producing E. coli in raw vegetables. The result showed that the prevalence of the isolates in raw vegetables was 62.78 (113/180), consisting of 62.11 (59/95) in green carol lettuce and 63.53 (54/85) in mung bean sprouts, whereas the microbial load ranged from 1100 MPN/g with median 9.2 MPN/g. Overall, the study showed that there was no significant difference (P>0.05) in the microbial density of the isolates in vegetable samples purchased from wet markets and hypermarkets. Furthermore, the antibiotic susceptibility test revealed that all related strains were susceptible to cefepime, piperacillin/tazobactam and meropenem. However, the resistance to ampicillin was shown by 80 of the isolates. The multiple antibiotic resistance (MAR) indices of ESBL-producing E. coli ranged from 0.1 to 0.6. The majority of the isolates (60) showed multidrug resistance. Hence, the current study suggested that raw vegetables could be a vehicle for the transmission of ESBL-producing E. coli to humans.